PRICE DYNAMICS OF LOCAL AND IMPORTED RICE IN RURAL AND URBAN MARKETS OF LAGOS STATE, NIGERIA - Bako, R. U.; Ibrahim, F. D.; Adebayo, C. O.; Mohammed, U. S. (Journal of Agripreneurship and Sustainable Development, 2021)
The study aimed at analyzing price dynamics of local and imported rice in Lagos State Nigeria. Analytical tools employed in the study include unit root test, Granger causality test and index of market concentration (IMC). The result revealed that all the price series became stationary after 1st differencing with an order of integration of I(1), implying that the prices of both local and imported rice in rural and urban markets were trending upwards in an irregular pattern. The Granger causality test result revealed a bi-directional causality relationship between all the price pairs as the null hypothesis was rejected at P≤0.01 level of probability. The IMC result shows a value of 2.795 and 2.581 for local and imported rice, respectively, indicating low short run relationship among. The study concluded that there is a feedback relationship between rural and urban market and existence of short run relationship between the markets in the study area. It was recommended that the flow of information should be enhanced between spatially separated markets and also firm policies should be implemented on prices to minimized irregularities in rice prices across board.